The Quality of Service at the International Corner in the Library of Universitas Muhammadiyah Sumatera Utara (UMSU) Based on the LibQUAL Model - Andini, Tias; Sayekti, Retno (FKIP - Universitas Riau, 2025)
This study aims to evaluate the service quality of the International Corner at the University of Muhammadiyah North Sumatra Library using the LibQUAL model. A quantitative descriptive method was applied with three dimensions of assessment: Affect of Service, Information Control, and Library as Place. Data were gathered through questionnaires distributed to 99 respondents and analyzed using Adequacy Gap (AG) and Superiority Gap (SG) values. Findings show that the average perception score (3.31) is above the minimum expectation (3.19) but below the ideal expectation (3.97). The Library as Place dimension achieved the highest performance (AG = +2.00; SG = +0.66), indicating user satisfaction with the environment and facilities. The Affect of Service dimension showed a positive AG (+0.43) but a slightly negative SG (–0.06), suggesting the need for improved librarian responsiveness. Meanwhile, the Information Control dimension had the lowest scores (AG = –1.41; SG = –2.16), indicating challenges in accessing international information resources. Overall, while the services meet users' basic needs, enhancements in information access and staff support are essential to meet ideal expectations and better support academic activities and the university’s internationalization goals.